Open innovation: the case of small and new financial technology firms in Brazil - Bussmann, Luis Alberto Scandelari (2020)
The term “open innovation” coined in 2003 by Chesbrough is receiving attention by the academy, and is frequently mentioned in the media. In a word more and more connected, there is an abundance of ideas and knowledge being created every day and becoming available. They can be imported and used within firms that didn’t necessarily participate in the creation of such ideas, or exported for use by firms outside of the one where the ideas and knowledge were created. But are the term and concepts related to Open Innovation used by firms in Brazil? A recent study reached the conclusion that this is not the case, that Open Innovation is weakly used and that Brazilian firms in the industrial sector with significant R&D activities don’t actually understand the concepts behind Open Innovation. Would the same also apply to Services? To begin with, the literature points to a deficiency in Open Innovation studies as they relate to services. Furthering it, very few studies on Open Innovation in financial services exist. Based on the opportunities presented by the literature, this study investigates small and new financial services firms in Brazil, evaluating why and how the concepts of Open Innovation are used, as well as identifying benefits and challenges firms face when implementing Open Innovation. To reach the proposed objectives, the study used an exploratory qualitative design based on multiple case study where senior level executives in small and new financial service firms in Brazil (FinTechs) were interviewed so as to collect their perceptions and perspectives on the subject. Results promote a better understanding on the usage of Open Innovation in Brazil, particularly in small and new financial service firms. Main findings include a set of open innovation practices actually used by startups, the four pillars guiding the implementation of their innovation model, the realization that execution thumps ideas in the world of startups, how startups shortcut their product creation process and bring about agility. We also found how legal matters, market culture and regulation, pressures for scaling and revenue growth act as challenges to implementing open innovation.